2008
DOI: 10.1017/s1368980007000870
|View full text |Cite
|
Sign up to set email alerts
|

Validity of photographs for food portion estimation in a rural West African setting

Abstract: Objective: To validate food photographs for food portion size estimation of frequently consumed dishes, to be used in a 24-hour recall food consumption study of pregnant women in a rural environment in Burkina Faso. This food intake study is part of an intervention evaluating the efficacy of prenatal micronutrient supplementation on birth outcomes. Subjects: Women of childbearing age (15-45 years). Design: A food photograph album containing four photographs of food portions per food item was compiled for eight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
75
3
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(86 citation statements)
references
References 17 publications
6
75
3
2
Order By: Relevance
“…The small bias for rice is important because it is the staple food and so the main source of energy. Only one other study measured agreement using κ w and it found better agreement than our study (κ w = 0·60 compared with κ w = 0·39) (34) .…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…The small bias for rice is important because it is the staple food and so the main source of energy. Only one other study measured agreement using κ w and it found better agreement than our study (κ w = 0·60 compared with κ w = 0·39) (34) .…”
Section: Discussioncontrasting
confidence: 59%
“…To illustrate this, a non-systematic review of studies that did report agreement between weighed and recalled methods is summarised in Table 1 (34)(35)(36)(37)(38)(39) . No studies were available from South Asia and only one study reported LOA in terms of nutrient intakes.…”
mentioning
confidence: 99%
“…However, similar high energy intakes have been published before by Mennen et al (2000) who investigated the habitual diet of rural Cameroonian women (3,896 kcal/ day). A photo book could have helped the women to better estimate portion sizes, though, as common in many parts of Africa, most women eat from a common pot, which makes estimates of portion size difficult even with a photo book (Huybregts et al 2008). Notwithstanding these high energy intakes, most of the women did not meet multiple EARs for micronutrient intakes, which would have even been worse in the case of lower energy intake.…”
Section: Discussionmentioning
confidence: 99%
“…The latter study showed a tendency to overestimate small portions and underestimate large portions. Huybregts et al (16) assessed the validity of using food photographs depicting foods in four different portion sizes among 15-45-year-old women in rural Burkina Faso. The women were served portions with the same weight as one of the photographs and the following day they were asked to estimate the portion sizes with the aid of the photographs.…”
Section: Discussionmentioning
confidence: 99%